Beyond the Panama Papers. The Performance of EU Good Governance Promotion The Anticorruption Report, volume 4 - Mungiu-Pippidi, Alina; Warkotsch, Jana (The Anticorruption Report, 2017)
This last title in the series covers the most important findings of the five yearsEU sponsored ANTICORRP project dealing with corruption and organized crime.How prone to corruption are EU funds? Has EU managed to improve governancein the countries that it assists? Using the new index of public integrity and avariety of other tools created in the project this issue looks at how EU funds andnorms affected old member states (like Spain), new member states (Slovakia,Romania), accession countries (Turkey) and the countries recipient of developmentfunds (Egypt, Tanzania, Tunisia). The data covers over a decade of structuraland development funds, and the findings show the challenges to changing governanceacross borders, the different paths that each country has experiencedand suggest avenues of reforming development aid for improving governance.